BIODIVERSITAS FUNGI MAKROSKOPIS DI SEKITAR KAWASAN CAGAR ALAM TANJUNG LAKSAHA PULAU ENGGANO BENGKULU - Welly Darwis; Ulandasari Ulandasari; R.H. Wibowo; Sipriyadi Sipriyadi; R.R.S. Astuti (Bioedukasi: Jurnal Pendidikan Biologi FKIP UM Metro, 2020)
Enggano is one of the outermost islands in Indonesia, located in Bengkulu province, South Bengkulu district. Biodiversity in the area around the nature reserve is very varied, ranging from plants, animals, and microorganisms.Macroscopic fungi biodiversity research has been conducted around the area of Tanjung Laksaha Banjarsari Enggano Nature Reserve in September 2018 to February 2019. The method used in this study is the roaming method and the data obtained were analyzed descriptively qualitatively. 75 species of macroscopic fungi from 3 phyla, 4 classes, 11 orders, 26 families, and 43 genera were found. Macroscopic fungi that are found generally live on weathered wood as many as 57 species, on 13 species of soil litter and 5 species of leaf litter.